2021
DOI: 10.1038/s41598-021-00948-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the COVID-19 prevalence and mortality using a novel data-driven hybrid model based on ensemble empirical mode decomposition

Abstract: In this study, we proposed a new data-driven hybrid technique by integrating an ensemble empirical mode decomposition (EEMD), an autoregressive integrated moving average (ARIMA), with a nonlinear autoregressive artificial neural network (NARANN), called the EEMD-ARIMA-NARANN model, to perform time series modeling and forecasting based on the COVID-19 prevalence and mortality data from 28 February 2020 to 27 June 2020 in South Africa and Nigeria. By comparing the accuracy level of forecasting measurements with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In addition to this, the ANFISE boosted the performance of FFNN, ANFIS, SVM, and MLR by 13, 6.1, 13.9, and 19.3 per cent, respectively. These numbers show that the capacity for the prediction of COVID-19 was increased in the case of the ensemble models rather than the single models, and these findings were compared to the findings of studies conducted in different fields using AI ensemble models [ 6 , 14 , 35 , 37 ]. Hence, these findings showed that ensemble models can be applied to the prediction of COVID-19 in the eastern Africa region more effectively than the single AI-driven models.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to this, the ANFISE boosted the performance of FFNN, ANFIS, SVM, and MLR by 13, 6.1, 13.9, and 19.3 per cent, respectively. These numbers show that the capacity for the prediction of COVID-19 was increased in the case of the ensemble models rather than the single models, and these findings were compared to the findings of studies conducted in different fields using AI ensemble models [ 6 , 14 , 35 , 37 ]. Hence, these findings showed that ensemble models can be applied to the prediction of COVID-19 in the eastern Africa region more effectively than the single AI-driven models.…”
Section: Resultsmentioning
confidence: 85%
“…These ensemble techniques have been applied in various studies for purposes such as the clustering and classifications of medical data, web ranking, economic forecasting, etc. [ 34 , 35 , 36 , 37 , 38 , 39 ]. Considering this situation, this study also applied the ensemble technique to predict COVID-19 mortality in East Africa.…”
Section: Methodsmentioning
confidence: 99%
“…In the third step, different white noise series are used to repeat the first and second steps, and the results are added to the original time series each time. Finally, the set of IMF items in the EMD method is averaged ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the above EEMD-based prediction methods can improve prediction accuracy, the use of simple linear or non-linear models in the choice of prediction methods still leads to the omission of the characteristic laws implied by the component series. For this, Wang et al [43] used a non-linear autoregressive artificial neural network (NARANN) to model each IMF term of COVID-19 prevalence and mortality decomposed by EEMD, and an autoregressive integrated moving average model (ARIMA) to model the residual term to capture the non-linear and linear features of the component series, respectively, which can better fit the dynamic dependence of the epidemic time series. Thus, motivated by the EEMD-based decomposition-integration idea, capturing the features implied by the component sequences with an appropriate hybrid model is an available way to improve the model's performance.…”
Section: Literature Reviewmentioning
confidence: 99%